Graphene-Enabled Tunable Phase Gradient Metasurface for Broadband Dispersion Manipulation of Terahertz Wave - Yin Zhang; Yijun Feng; Junming Zhao (Micromachines, 2023)
With the increasing demand for the miniaturization and flexibility of optical devices, graphene-based metasurfaces have emerged as a promising ideal design platform for realizing planar and tunable electromagnetic or optical devices. In this paper, we propose a tunable metasurface with low-dispersion phase gradient characteristics that is composed of an array of double-layer graphene ribbons sandwiched with a thin insulating layer and a polymer substrate layer with a gold ground plane. As two typical proof-of-concept examples, metasurfaces act as a planar prism and a planar lens, respectively, and the corresponding performances of tunable broadband dispersion are demonstrated through full-wave simulation experiments. By changing the Fermi level of each graphene ribbon individually to introduce abrupt phase shifts along the metasurface, the broadband continuous dispersion effect of abnormal reflection and beam focusing is achieved within a terahertz (THz) frequency region from 3.0 THz to 4.0 THz, and the dispersion results can be freely regulated by reconfiguring the sequence of Fermi levels via the bias voltage. The presented graphene metasurface provides an avenue for the dispersion manipulation of a broadband terahertz wave and may have great prospects in the fields of optics, imaging, and wireless communication.